PSYCHOLOGICAL CONFLICT OF THE MAIN CHARACTERS IN THE MOVIE VIVARIUM (2020) - Faiz, Khansa (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to analyze the psychological conflict experienced by the main characters in the movie